AVALIAÇÃO DA CULTURA DE SEGURANÇA DOS ALIMENTOS EM SERVIÇOS DE ALIMENTAÇÃO EM PROCESSO DE CATEGORIZAÇÃO - Penna, Maíra de Oliveira (2024)
The categorization of food services is a globally applied tool that aims to assist in ensuring food safety by transforming handling practices. The attitudes of food handlers are deeply influenced by the set of behaviors, beliefs, and values that make up the organization, integrating into the Food Safety Culture (FSC). Therefore, this study aimed to assess the FSC in food services undergoing categorization, as well as discuss the classification of FSC in relation to the characteristics of the food services and sanitary risk. The study, conducted from September to December 2023, evaluated the FSC in five food services in Santa Maria, Brazil, during the categorization process. The assessment was carried out by three nutritionist researchers with experience in food safety and involved three main stages: training and method selection, the application of questionnaires and participant observation, and qualitative and quantitative data analysis. The data analysis followed a triangulation method to determine the predominant FSC, and the food services were categorized into categories A, B, and C, where A corresponded to services that excellently met the requirements; B, for services that met the requirements very well; and C, for services that met the requirements satisfactorily. The five food services evaluated showed an overall result of active-proactive FSC (2-3), with a risk score in the categorization ranging from 34 to 97, classifying them in categories B and C. The study identified that an active-proactive FSC was aligned with the categorization of food services, resulting in satisfactory sanitary risk scores. The food services varied in operational time (6 months to 27 years), number of handlers (6 to 9), and managers (1 to 6), as well as the type of meals offered (delicatessen, buffet, butcher shop, snack bar). Communication was the most proactive element (3.0; 2.7; 2.5; 2.8; 3.0, respectively), and risk perception was the most reactive element (2.1; 2.0; 2.1; 1.6; 2.3, respectively). Active-proactive leadership by the managers was also essential, as it promoted an appropriate work environment and greater commitment to food safety. However, a low risk perception among food handlers was identified as a common vulnerability, compromising the proactivity of the FSC. To maintain and continuously improve food safety standards, it is essential to conduct research on FSC in food services undergoing categorization, enabling the implementation of best practices and the adaptation of regulations to new realities in the sector.